Are World Championship participation and seed status predictors of Olympic success in judo? - Kons, R. L.; Conceição-Santos, D. F.; Santos do Carmo, E. F.; da S. Athayde, M. S.; Agostinho, M. F.; Lopes-Silva, J. P.; Takito, M. Y.; Detanico, D.; Franchini, E. (Managing Sport and Leisure, 2025)
The Olympic Games and World Championships are key competitions in judo, with athletes aiming to secure medals in these prestigious events. The three-year Olympic cycle for Paris 2024 likely intensified the preparation period for elite judo athletes, with some classification to the Olympic Games being defined a few months before its starting. This study examined the role of World Championship results and seeding status in predicting success at the 2024 Olympics. Data from 738 athletes (390 males, 348 females) were analyzed using official records from the International Judo Federation. Logistic regression assessed the association between World Championship participation, seed status, and Olympic medal outcomes. Results showed that both skipping the World Championships 2024 and winning a medal at this event were associated with significantly higher odds of Olympic medal achievement (OR = 2.48 [95% CI = 1.19-5.16], p = 0.015; OR = 3.86 [95% CI = 1.64-9.07], p = 0.002) compared to disputing the World Championships 2024, but not winning a medal. Additionally, seeded athletes had 5.45 times the odds of winning a medal compared to non-seeded athletes (95% CI = 2.63-10.60, p < 0.001). These findings suggest that skipping the World Championships 2024 combined with seeding status may offer strategic advantages.